Середньотрипільське поселення Сосни на р. Згар - Гусєв, С.О. (Археологія, 2001)
У статті охарактеризовано матеріали поселення трипільської культури етапу ВІІ Сосни. Висловлено міркування щодо тимчасового мешкання трипільців у Соснах у період освоєння середньобузького регіону. Среднетрипольское поселение у с. Сосны Литинского р-на Винницкой обл. занимало небольшой по площади (3—4 га) поврежденный карьером мысообразный останец левого берега р. Згар. В культурном слое незначительной толщины (до 5 см) обнаружены и раскопаны два углубленных жилища земляночного типа, собрано значительное количество кремниевых орудий труда, разнообразную столовую и кухонную керамику, зооморфную и антропоморфную пластику. Типологическое, морфологическое и трансологическое изучение культурных остатков, а также использование палеоботанических и палеозоологических данных позволило отнести поселение Сосны к ворошиловскому типу трипольских памятников этапа ВІІ Среднего Побужья и рассматривать его как временное поселение на период освоения западнотрипольскими племенами данного региона. The mid-Trypillian settlement near the village of Sosny in the Litynsky district of the Vinnytsya region occupied a small area (3–4 hectares) of a cape-like outlier, which is damaged by the open pit, on the left bank of the river of Zgar. In the cultural layer of a small thickness (up to 5 cm), two deepened dwellings were found and excavated. A significant amount of flinty and stone tools, various table and kitchen ceramics, and zoomorphic and anthropomorphous plastic things were gathered. The typological, morphological, and tracing investigation of the cultural remains as well as the use of palaeobotanic and palaeozoological data allows us to refer the settlement of Sosny to the Voroshylivka type of Trypillian monuments of the stage VII in the Middle Bug region and to consider it a temporary settlement in the period of mastering of this region by west-Trypillian tribes.